Bioprospecting of Actinomycetes from Diverse Ecosystems for Antimicrobial Activity - Godbole, Amita Prasanna; Wadetwar, Rita Naresh; Bundale, Sunita Bhupesh; Nashikkar, Nandita; Kanojiya, Pranita Sunil (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Actinomycetes are unique and ubiquitous organisms in nature and are historically holding first position as one of the major antibiotic producers. The aim of the study was screening and pre-treatments of soil, marine, and mangrove samples for isolation of antibiotic producing actinomycetes. Materials and Methods: Actinomycetes were isolated from pre-treated soil, marine, and mangrove samples using different isolation media. They were assessed for antimicrobial activity by cross streak and agar well diffusion method. Colony characteristics, growth pattern and microscopy were performed for partial characterization of the isolates. Promising isolates were identified by 16S rRNA genomic analysis and deposited in GenBank. Results: Study led to the isolation of 109 actinomycete isolates. In the microbiological studies, 19 isolates showed a potent inhibition against E. coli, 17 isolates showed activity against S. aureus, 10 isolates exhibited activity against K. pneumoniae and B. subtilis each, and 9 isolates showed activity against C. albicans. The results revealed that most of the isolates belonged to Streptomyces genus. Less than 10% isolates belonged to non-Streptomyces genera. The broad-spectrum antimicrobial activity against all the test organisms was exhibited by 6 soil isolates designated as D, D2, F30 (brown pigment), TS13 (pink), TS14 (green), TS4 (cherry red), and 5 marine isolate M1, M7 (pink), M10, M14, M11 (yellow). Conclusion: Our findings highlights that the West coast and mangrove forest of Maharashtra are attractive sites to knock out the biologically active and undiscovered species of actinomycetes having potential to produce novel antibiotic.
Keywords: Actinomycetes; Bioactive Metabolites; Biodiversity; Marine ecosystems; Antimicrobial activity; 16S rRNA